Development in Sub-Saharan Africa New Micro-Level Evidence on Education, Geography and Trade - Wild, Frederik (2024)
This dissertation contributes to the understanding of three pertinent developmental challenges in sub-Saharan Africa, namely education, geography, and trade. More specifically, it presents three independent and self-contained chapters which analyze these factors from a micro-level perspective, in turn. After a brief introduction in Chapter 1, Chapter 2 re-visits the role of physical geography in economic development. In particular, it employs a large-scale geo-referenced household-level survey covering 28 sub-Saharan African countries over 20 years to analyze the previously established link between coastal access and individual living standards. Analyzing individual-level data allows to expand on the insights from cross-country and cross-regional contexts and also facilitates the analysis of potential channels. The results show that individuals living further away from the coast are significantly poorer, as measured along a breadth of welfare indicators, such as basic consumption (water, food, medical care), possession of various consumer durables, or having paid employment. The chapter highlights the role of human capital, urbanization as well as infrastructural endowments in explaining the identified within-country differences in individual economic welfare. Chapter 3 investigates the effect of education on women's fertility and contributes to a growing literature which analyzes this nexus via quasi-experimental methods. Specifically, it leverages Burundi's Free Primary Education Policy of 2005 to identify exogenous variation in schooling via a Regression Discontinuity Design (RDD) and analyzes the outcomes affected by schooling through an instrumental variable (IV) approach. The results confirm the negative relationship between schooling and fertility observed in other developing settings. However, contrary to extant studies, the chapter provides novel evidence on a differential treatment effect of education. While poor women profit from policy-induced education in terms of increases in literacy, remunerated employment opportunities as well as a reduction in teenage births, none of these effects of additional education are observed for women from the wealthier households of our sample. The evidence of such a marked heterogeneity helps to evaluate under which conditions the literature’s previous findings may generalize. Chapter 4 evaluates the distributional effects of trade liberalization in Africa by combining the spatial considerations of regional market integration with a household-level analysis. The chapter thereby treats the re-establishment of the East African Community (EAC) in 2001 as a regional policy intervention having differential effects on individual households governed by their geo-spatial location within the countries. This prediction is derived from an extension to a canonical New Economic Geography (NEG) developed in the chapter. Contrary to the model’s prediction, the empirical results drawn from a difference-in-differences (DiD) approach do not reveal relative welfare increases in regions closer to internal EAC borders. Rather, the results provide evidence of strengthened agglomeration tendencies in the pre-existing economic hubs of Nairobi, Dar es Salaam and Kampala, as measured by an increase in consumption and population density.
Keywords: Economic development; Sub-Saharan Africa; Education; Geography; Trade